2021
DOI: 10.1002/imhj.21951
|View full text |Cite
|
Sign up to set email alerts
|

Maternal caregiving representations of the infant in the first year of life: Associations with prenatal and concurrent reflective functioning

Abstract: Few studies have examined whether maternal caregiving representations are associated with maternal reflective functioning (MRF), especially when MRF is evaluated longitudinally beginning in pregnancy. This study addresses this gap by evaluating whether prenatal and postnatal MRF are associated with mothers’ caregiving representations assessed at 7 months postpartum, and by exploring theoretically unexpected MRF scores in each of the representational categories. Forty‐seven mothers were recruited during their l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…Recent reviews that have explored the associations between pre- and postnatal bonding have highlighted that the complex pathways likely to exist in these associations are still unclear [ 2 , 15 , 17 ]. Considering other factors, such as parental mentalization, could provide a deeper understanding of the variables that influence the establishment of the maternal affective tie with the fetus and subsequently with the newborn [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews that have explored the associations between pre- and postnatal bonding have highlighted that the complex pathways likely to exist in these associations are still unclear [ 2 , 15 , 17 ]. Considering other factors, such as parental mentalization, could provide a deeper understanding of the variables that influence the establishment of the maternal affective tie with the fetus and subsequently with the newborn [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…As Alvarez-Monjarás et al [ 19 ] recently showed, it is the development of a mother’s capacity for reflecting upon the child’s mental states that allows the parent to display more appropriate and sensitive responses to the child’s behavioral cues. Therefore, higher maternal PRF is related to more positive maternal caregiving behaviors [ 18 , 19 , 38 ]. However, the link between caregiving experiences and maternal PRF has not been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%
“…The sociodemographic factors examined across studies typically include income level, education level, maternal age, and single parenthood. Multiple studies have documented significant associations between level of parental education and PRF (Alismail et al., 2022; Arkle et al., 2023; Benbassat & Priel, 2012; Brophy‐Herb et al., 2023; Halfon & Besiroglu, 2020; Huber et al., 2015; Lowell et al., 2022; Newman‐Morris et al., 2020; Sleed et al., 2018; Stover & Kiselica, 2014). Similarly, a significant association between maternal income level and PRF has been reported in at least four studies (Arkle et al., 2023; Brophy‐Herb et al., 2023; Sleed et al., 2018; Yatziv et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…These findings are not consistent with many other studies. While some studies do show depression and P‐PRF and PRF are not associated (Alismail, 2017), many studies have found these associations. Symptoms of depression (Condon & Corkindale, 1997; Huth‐Bocks et al., 2004), anxiety (Bateman & Fonagy, 2012; Nolte et al., 2011) and adverse childhood events (Håkansson et al., 2018; Yu et al., 2020) feature deficits in mentalizing.…”
Section: Discussionmentioning
confidence: 99%